Dampak Verbal Bullying Terhadap Kepercayaan Diri Siswa SD Negeri 010 Bukit Kauman Kecamatan Kuantan Mudik - Melsa Marsela; Fitriyeni (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2024)
Verbal bullying is defined as the act of bullying or insulting someone by using unheard words to make fun of, insult, or say unpleasant or inappropriate things. Victims of verbal bullying typically experience negative effects on their school, mental health, and social interactions. This study aims to determine the impact of verbal bullying on students' confidence in SD Negeri 010 Bukit Kauman, Kuantan Mudik District. The method used in this study used quantitative descriptive and was carried out at SD Negeri 010 Bukit Kauman, Kuantan Mudik District. The study used a sample of all 66 students. This research method uses questionnaires and interviews, after the data is obtained the data is analyzed with a quantitative descriptive approach with percentage data. Based on the results of research, verbal bullying has a serious impact on a person's self-confidence, with details of the level of self-confidence of students who are in the high category including 10 students (19.61%), then in the medium category has a frequency of 33 students (64.71%), and the lace category there are 8 students (15.69%).